Hak Anak Akibat Perceraian Berdasarkan Undang-Undang Perkawinan Dan Kompilasi Hukum Islam - Luluk Septaniar Triyanita; Paramita Prananingtyas (Notarius, 2023)
AbstractAnalyzing children's rights after parents' divorce and the legal consequences for parents who are less responsible for caring for children, based on Law Number 16/2019 concerning Amendments to Law Number 1/1974 concerning Marriage and Compilation of Islamic Law. This study aims to analyze the perspective of Law No. 16/2019 concerning Amendments to Law No. 1/1974 and the Compilation of Islamic Law related to fulfilling child custody after divorce, as well as analyzing the legal consequences for divorced parents based on this Law for negligence in fulfilling children's rights. The research method used is normative juridical. The results of the study concluded that Law No. 16/2019 concerning Amendments to Law No. 1/1974 clearly pays attention to fulfilling a number of children's rights properly, both in situations of intact husband and wife relationships and after divorce. There are consequences for parents who are negligent in the hadhanah obligation, with the implication of revoking the parent's control rights over the child. Keyword: due to divorce; children's rights; hadhanahAbstrakMenganalisis hak anak setelah perceraian orang tua dan konsekuensi hukum bagi orang tua yang kurang bertanggung jawab dalam pemeliharaan anak, berdasarkan Undang-Undang Nomor 16/2019 tentang Perubahan Atas Undang Nomor 1/1974 tentang Perkawinan dan Kompilasi Hukum Islam. Penelitian ini bertujuan menganalisis perspektif UU No 16/2019 tentang Perubahan Atas UU No 1/1974 dan Kompilasi Hukum Islam terkait pemenuhan hak asuh anak setelah perceraian, serta menganalisis konsekuensi hukum bagi orang tua yang bercerai berdasarkan UU tersebut terhadap kelalaian dalam pemenuhan hak anak. Metode penelitian yang dipergunakan yakni yuridis normatif. Hasil penelitian menyimpulkan bahwa UU No 16/2019 tentang Perubahan Atas UU No 1/1974 dengan jelas memperhatikan pemenuhan sejumlah hak anak dengan baik, baik dalam situasi hubungan suami istri yang utuh maupun setelah bercerai. Terdapat konsekuensi bagi orang tua yang lalai dalam kewajiban hadhanah, dengan implikasi pencabutan hak penguasaan orang tua terhadap anak tersebut.Kata kunci:  akibat perceraian; hak anak; hadhanah